The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/s002329900405
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by Isoproterenol on Carbachol-induced K + and Cl − Currents and Fluid Secretion in Rat Parotid

Abstract: Isoproterenol (IPR) and 8-(4-chlorophenylthio)-cyclic AMP (cpt-cAMP) enhanced carbachol (CCh)-induced fluid secretion from rat parotid glands, but had no effect by themselves. The enhancement by IPR was blocked by propranolol. In dispersed parotid acinar cells, IPR and cpt-cAMP potentiated CCh-induced K+ and Cl- currents (IK and ICl). IPR at the concentration of 0.1 microM significantly potentiated the CCh-induced increase in intracellular Ca2+ concentration ([Ca2+]i), but 1 mm cpt-cAMP did not. The incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…The Ca 2+ -sensitive adenylyl cyclase (type 8) is reported to be critical for accumulation of cAMP in mouse parotid acinar cells (Watson et al 2000 An interaction between the cAMP and the Ca 2+ signal has been reported to regulate various cellular functions. In salivary glands, cAMP modulates Ca 2+ entry (Tanimura et al 1999;Nakahari et al 2000), K + and Cl _ channels (Ishikawa, 1997), fluid secretion (Hirono et al 1998) and exocytosis (Yoshimura & Nezu, 1992;Nakahari et al 2000), which are all activated by increases in [Ca 2+ ] i . While these studies showed that cAMP modulates the action of Ca 2+ , in our study Ca 2+ modulates the action of cAMP.…”
Section: Figure 10mentioning
confidence: 99%
“…The Ca 2+ -sensitive adenylyl cyclase (type 8) is reported to be critical for accumulation of cAMP in mouse parotid acinar cells (Watson et al 2000 An interaction between the cAMP and the Ca 2+ signal has been reported to regulate various cellular functions. In salivary glands, cAMP modulates Ca 2+ entry (Tanimura et al 1999;Nakahari et al 2000), K + and Cl _ channels (Ishikawa, 1997), fluid secretion (Hirono et al 1998) and exocytosis (Yoshimura & Nezu, 1992;Nakahari et al 2000), which are all activated by increases in [Ca 2+ ] i . While these studies showed that cAMP modulates the action of Ca 2+ , in our study Ca 2+ modulates the action of cAMP.…”
Section: Figure 10mentioning
confidence: 99%
“…InsP 3 R2 is the major InsP 3 R isoform in many cell types, including hepatocytes (7,8), astrocytes (9,10), cardiac myocytes (11), and exocrine acinar cells (8,12). Activation of PKA has been demonstrated to enhance InsP 3 -induced Ca 2ϩ signaling in hepatocytes (13) and parotid acinar cells (4,14). Although PKA phosphorylation of InsP 3 R2 is a likely causal mechanism underlying these effects, the functional effects of phosphorylation have not been determined in cells unambiguously expressing InsP 3 R2 in isolation.…”
mentioning
confidence: 99%
“…Indeed, the dilute secretion elicited by parasympathetic stimulation in situ (or muscarinic cholinergic agonists in vitro) contains a protein content, whereas the protein-rich, low volume secretion produced by ␤-adrenergic agonists contains fluid and electrolytes. Furthermore, parasympathetically and sympathetically controlled signaling pathways are synergistic in enhancing the rates of protein export and fluid and electrolyte transport (4,(7)(8)(9)(10). Thus alone and in combination, the signaling pathways enable acinar cells to vary the amount and composition of saliva over a wide range.…”
mentioning
confidence: 99%